Young people's perceptions of substance use norms and attitudes in the LGBT community - Daniel Demant; Leanne M. Hides; David J. Kavanagh; Katherine M. White (Elsevier, 2021)
Abstract Objectives: Sexual minority young people (SMYP) show higher levels of substance use than their heterosexual counterparts. This study aims to test potential LGBT community‐specific reasons assumed to affect substance use and their relationships to LGBT community participation/connectedness and substance use behaviour. Methods: Eight LGBT community‐specific reasons for substance use were tested in an online survey with 1,556 SMYP. Results: Respondents agreed that the LGBT community had liberal attitudes towards substance use (80.5%, n=1,079) and that the media portrayed substance use as a part of the community culture (66.5%, n=904). Participants disagreed that excessive partying is a part of the community (34.7%, n=470). Significant but weak correlations between reasons and community participation/connectedness or personal substance use behaviour were found. Subgroup analyses indicated male and gay/lesbian participants showed differential agreement levels to some of the reasons. Conclusion: Young people's perceptions of substance use within the LGBT community are not associated with community participation/connectedness or personal substance use. Implications for public health: Further research is needed to better understand what factors lead to elevated levels of substance use in SMYP. This may assist in the development of adequate public health responses. Targeting problematic beliefs may have little impact on substance use in SMYP.